The menopausal hot flush: a review. (4th July 2017) - Sturdee, D. W.; Hunter, M. S.; Maki, P. M.; Gupta, P.; Sassarini, J.; Stevenson, J. C.; Lumsden, M. A.
Abstract: The hot flush is the most characteristic and often the most distressing symptom of the menopause. It is a unique feature and yet the mechanism and health implications are still not fully understood. This review summarizes some of the current thoughts on factors contributing to flushing, the physiological, vascular and neuroendocrine changes associated with flushing and the possible cardiovascular and other health implications for women experiencing hot flushes. Therapy is not discussed.